The Effect of Current Ratio (CR) and Debt To Equity Ratio (DER) on Return on Assets (RoA) in Pharmaceutical Subsector Companies Listed on the Indonesian Stock Exchange (IDX) 2020-2023 Period - Mursalini, Wahyu Indah; Nurhayati, Nurhayati; Azen, Muhamad (Journal of International Accounting, Taxation and Information Systems, 2025)
The primary objective of this research is to gather practical evidence concerning the impact of the Current Ratio and Debt To Equity Ratio on the Return On Assets in Pharmaceutical Subsector Companies listed on the Indonesia Stock Exchange (IDX) between 2020 and 2023. The research employs regression analysis using a quantitative methodology based on financial reports of the companies. The research sample was chosen through the purposive sampling technique, consisting of 26 pharmaceutical subsector companies that fulfilled the research criteria. The findings of the study suggest that the CR has a positive and influential influence on ROA, with a regression coefficient of 0.023 and a significance level of 0.000 (<0.05), hence confirming the hypothesis (H₁). Conversely, the DER is uninfluential on ROA, with a regression coefficient of 0.011 and a significance value of 0.596 (>0.05), leading to the rejection of hypothesis H₂. Nevertheless, both the CR and DER jointly is influential on the ROA, with an F value of 15.785 and a significance of 0.000, supporting the acceptance of hypothesis H₃. Hence, this study highlights the significant role of the CR in enhancing ROA, while the DER lacks individual significance.